Chemical treatments' effect on the structural and mecha-nical properties of polyvinyl alcohol/spent coffee ground composite films - Muhibbuddin, Muhibbuddin; Ilham, Farid; Muhammad, Ikramullah; Rizal, Samsul (Politeknik Negeri Lhokseumawe, 2025)
Chemical treatments are a common strategy for improving the compatibility of natural fillers with polymer matrices. However, their specific impact on Spent Coffee Grounds (SCG) as reinforcement for Polyvinyl Alcohol (PVA) composites remains unclear. This study investigates the effects of alkalization, bleaching, and acid hydrolysis on the structural and mechanical properties of PVA/SCG composite films. The SCG was treated with 10% NaOH, 10% NaOCl, and 1 M H₂SO₄. FTIR analysis showed that untreated SCG exhibited characteristic C–H stretching peaks at 2922 cm⁻¹ and 2853 cm⁻¹, corresponding to methyl and methylene groups in cellulose and hemicellulose. After alkalization and bleaching, these peaks nearly disappeared, indicating excessive removal of hemicellulose and lignin and suggesting structural degradation of the filler. In contrast, acid hydrolysis largely preserved these peaks, reflecting milder structural modification. Mechanical testing confirmed this trend: the untreated composite achieved the best performance, with tensile strength of 2.30 MPa and tear resistance of 2.12 N All chemically treated samples showed reduced strength and toughness, with alkalization being the most detrimental. These findings demonstrate that the decline in mechanical properties is directly correlated with structural damage detected by FTIR, emphasizing the need to optimize treatment severity.